Analysis and design of analog integrated circuits - Gray, Paul R., 1942; Hurst, Paul J.; Lewis, Stephen H.; Meyer, Robert G. (Chichester : John Wiley, 2009)
Intended both for students and as a reference for working engineers, the fifth edition of this popular engineering textbook is updated to include discussions of newly available integrated circuits as well as general advances in the field. Drawn from material taught to high level seniors and graduate students at the University of California's Berkeley and Davis engineering departments, the work covers such topics as the physics of bipolar and MOS transistors, the technology of integrated circuit (IC) fabrication and the design and uses of operational amplifiers as well as many advanced topics in IC principles and design. This volume makes extensive use of the SPICE mathematical and scientific analysis software and a working knowledge of that system is recommended for understanding and using the included example equations and schematics. Gray (emeritus, engineering dept UC Berkeley), Hurst (electrical engineering, UC Davis), Lewis (electrical engineering, UC Davis) and Meyer (emeritus, engineering, UC Berkeley) are preeminent scholars of modern integrated circuit technology. Annotation ò011 Book News, Inc., Portland, OR (booknews.com)
Models for integrated-circuit active devices -- Bipolar, MOS, and BiCMOS integrated-circuit technology -- Single-transistor and multiple-transistor amplifiers -- Current mirrors, active loads, and references -- Output stages -- Operational amplifiers with single-ended outputs -- Frequency response of integrated circuits -- Feedback -- Frequency response and stability of feedback amplifiers -- Nonlinear analog circuits -- Noise in integrated circuits -- Fully differential operational amplifiers.
Buku Bacaan Asas Fakulti
Previous ed.: New York; Chichester: Wiley, 2001.
Includes bibliographical references and index.
Keywords: Linear integrated circuits -- Computer-aided design; Metal oxide semiconductors -- Computer-aided design; Bipolar transistors -- Computer-aided design